Exploring the Effects of Macro-Environment on the Predisposition to Adopt Strategic Orientation among Small Medium Size Hotel Entrepreneurs - Kasim, Azilah; Dzakiria, Hisham (International Journal of Economics and Financial Issues, 2016)
This paper looks at the effect of macro-environment context on small and medium size hotels’ predisposition to adopt strategic orientation using a qualitative approach in its research methodology. Specifically it is based on in-depth interviews of fifteen informants representing the hospitality industry. Analysis from the themes surfaced suggests SME Hotels are operating within a political and financial business environment, which is found to be relatively unfriendly. However, the social and economic conditions for small and medium size hotels were encouraging. Against this background, SME Hotels operate by adopting some degree of entrepreneurial and/or market orientation. This paper offers meaningful findings to the study research questions which other methodology may not be able to provide. Keywords: Small and medium size hotels, macroenvironment, strategic orientations JEL Classification: M10, M14